Transfer Pricing in China - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China Briefing, The Practical Application of China Business, 2011)
This Guide is a detailed overview of all aspects of transfer pricing in China. Produced in association with Transfer Pricing Associates, a specialist global transfer pricing firm, this is an essential work for any businessman trading with or conducting business in China. The book deals with all aspects of transfer pricing from a practical perspective, from designing and implementing a transfer pricing system, to managing China compliance and preparing for an audit.